DATE PALM CULTIVATION IN INDIA: AN OVERVIEW OF ACTIVITIES - Shah, J. J. (Emirates Journal of Food and Agriculture, 2014)
The ancestry of date palm is reviewed with reference to the complex relationship existing between date palm (Phoenix dactylifera) and sugar date palm (P. sylvestris) during early introduction of the date palm into India, especially in Kutch, Gujarat. The cultivation practices of growing the date palm in important regions of India are described. Because of climatic limitations, it is impossible to fully ripen fruits on the trees; therefore, harvest is done at khalal stage with subsequent artificial ripening. The common varieties preferred for cultivation and their performance are reviewed. The institutions involved in activities of introducing imported cultivars and developing tissue culture plants from local varieties are detailed. Introductions of elite foreign cultivars have been successful, especially with respect of Barheecv. Studies are underway to assess the germplasm value of seedling date palms, and to establish tissue culture laboratories to propagate local varieties and imported cultivars. Because India is the world’s largest importer of dates, local production has strong potential to supply domestic markets and to create jobs in the dry areas of the northwest. Problems facing the cultivation of date palm in India are pointed out.